Responses of juvenile fathead minnow (Pimephales promelas) gut microbiome to a chronic dietary exposure of benzo[a]pyrene. (1st June 2021) - DeBofsky, Abigail; Xie, Yuwei; Challis, Jonathan K.; Jain, Niteesh; Brinkmann, Markus; Jones, Paul D.; Giesy, John P.
Abstract: The microbiome has been described as an additional host "organ" with well-established beneficial roles. However, the effects of exposures to chemicals on both structure and function of the gut microbiome of fishes are understudied. To determine effects of benzo[ a ]pyrene (BaP), a model persistent organic pollutant, on structural shifts of gut microbiome in juvenile fathead minnows ( Pimephales promelas ), fish were exposed ad libitum in the diet to concentrations of 1, 10, 100, or 1000 μg BaP g −1 food, in addition to a vehicle control, for two weeks. To determine the link between exposure to BaP and changes in the microbial community, concentrations of metabolites of BaP were measured in fish bile and 16S rRNA amplicon sequencing was used to evaluate the microbiome. Exposure to BaP only reduced alpha-diversity at the greatest exposure concentrations. However, it did alter community composition assessed as differential abundance of taxa and reduced network complexity of the microbial community in all exposure groups. Results presented here illustrate that environmentally-relevant concentrations of BaP can alter the diversity of the gut microbiome and community network connectivity. Graphical abstract: Image 1 Highlights : Dominant phyla of gut microbiome are consistent with those of other freshwater fishes. BaP metabolites and exposure doses were consistent with those found in contaminated sites. Dietary BaP exposure has significant, dose-dependent effects on the fish gut microbiome. Dietary BaP exposure altered association networks of gut microbiome. Abstract : Environmentally-relevant concentrations of BaP can alter the diversity of the gut microbiome and community network connectivity via dietary exposure route.